Education Between “Peace” and “Justice” in Times of Armed Conflict and Reconciliation – the Colombian Case - Meier, Markus D.; Páez, Manuel (International Dialogues on Education Journal, 2016)
This article deals with the role of education for peace building in the context of the Colombian post-conflict. It locates the former in the context of pragmatist and legalist approaches to post-conflict phases and analyses its “buffer role” between the two. A brief introduction to the history of the Colombian conflict is followed by theoretical considerations about educational aspects of the armed conflict and the educational requirements for successful “phases of transition”. The problem of the fragile balance between “supporting the victim” and “reintegrating the victimizer” is seen as a systemic challenge to the community, but also to society at large. Conclusively, the problem of “pedagogical stagings” is discussed in this context.